Toward a sustainable food system: Reducing food loss and waste - Schuster, Monica; Torero, Máximo (International Food Policy Research Institute, 2016)
Reducing food loss and waste can contribute to food security and sustainability. Measuring food loss and waste, identifying where in the food system it occurs, and developing effective policies along the value chain are essential first steps toward addressing the problem.